The Communion of the Apostles and the Spiritual Eucharist in the Religious Thought and Art of the Old Believers - Sulikowska, Aleksandra (Religions, 2022)
The division that occurred in the Patriarchate of Muscovy in the middle of the 17th century resulted in a large part of the believers being alienated from the clergy; in consequence, many communities of the Old Believers, who had come to terms with this loss, renounced most of the sacraments, including the Eucharist. This situation impacted the art of the Old Believers, especially in the Priestless Old Believer communities, for instance, in the interiors of their houses of prayer, where the presbytery area disappeared, and the iconostasis changed its function. This article contains an analysis of how one of the old iconographic themes connected with the Eucharist, namely the Communion of the Apostles, functioned in the Old Believer setting. Sources originating from those circles, especially the 18th-century Pomorian Answers (Pomorskie otvety), indicate that the Old Believers saw the Eucharist as a spiritual experience—the only one that was available to the faithful who lived in communities that lacked a clergy. This is most probably the context in which, for instance, Old Believer versions of the Communion of the Apostles should be understood. The view of the Old Believer identity, and Old Believer art, as proposed in this article takes under consideration not only the tradition but also the change, which was an unavoidable part of their communities’ experience, and which may also constitute an essential key to our reading of the contents and meaning of Old Believer icons.